Accuracy improvement for RLLLR five-axis machine tools: A posture and position compensation method for geometric errors. (November 2021) - Liang, Ruijun; Wang, Zhiqiang; Chen, Weifang; Ye, Wenhua
Abstract: Compensating geometric errors on machine tools requires further improvement for the purpose of high accuracy, because most current methods only focus on positions of cutting points, while ignoring vector errors of the rotary axes' postures; and they usually use the calculated compensation values to directly modify NC commands or axial movements, without considering the errors that the compensated movements themselves would create. This paper proposes a novel compensation method that includes both position and posture errors of the tool center point of a RLLLR five-axis machine tool. First, the position and posture errors are modeled through the multi-body system kinematics of the five-axis machine. Second, both kinds of errors are compensated in an off-line way that compares the coordinates and angles point by point through iterations, thus the extra errors that compensated results generate can be eliminated. The iteration process is terminated under control of the allowable error range. Posture errors are first compensated through correcting the angles of the rotary axes, and then position errors are corrected by modifying TCP's coordinates. Third, a program that incorporates the error molding and the compensation algorithms are developed. It can automatically complete the process of calculating error matrices, identifying parameters and outputting commands. Finally, the comparison experiments were conducted on the linear axes' linear and arc movements, as well as the rotary axes' rotating movements, and the results validated that the proposed method could effectively improve geometric accuracy. Highlights: Compensating of tool posture error and TCP position error for five-axis machine tool Correction via NC code for axes position by point-by-point comparison and iteration Integrating of the algorithms of error modeling and compensation into a program Validation for compensation to linear interpolation or rotary axis using a ball-bar